1941
DOI: 10.1085/jgp.24.5.597
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Cell Metabolism and Cell Division

Abstract: 1. An enzyme capable of oxidizing reduced cytochrome c (i.e. a cytochrome oxidase) has been obtained from Arbacia eggs. In 0.02 M hydroquinone, the cytochrome oxidase was half activated at a cytochrome c concentration of approximately 4 x 10–6 M. The concentration of the cytochrome oxidase was found to be nearly the same in unfertilized and fertilized eggs, the amount of the enzyme—as measured by means of its activity toward cytochrome c as a representative substrate—being more than sufficient to account for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1942
1942
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Relationship of caffeine concentration to the degree of cleavage in- cytochrome oxidase point from the evidence of Krahl, Keltch, Neubeck, and Clowes (1941) and others. I have no direct evidence that caffeine acts specifi- cally on the cytochrome oxidase enzyme but it should be noted that the caffeine maximum inhibition of 02 consumption is above 60 per cent and cyanide maximum inhibition is above 70 per cent.…”
Section: ___ _~mentioning
confidence: 93%
See 1 more Smart Citation
“…Relationship of caffeine concentration to the degree of cleavage in- cytochrome oxidase point from the evidence of Krahl, Keltch, Neubeck, and Clowes (1941) and others. I have no direct evidence that caffeine acts specifi- cally on the cytochrome oxidase enzyme but it should be noted that the caffeine maximum inhibition of 02 consumption is above 60 per cent and cyanide maximum inhibition is above 70 per cent.…”
Section: ___ _~mentioning
confidence: 93%
“…Ball and Meyerhof (1940) indicated the presence of an oxidative enzyme upon which respiratory inhibitors act in unfertilized Arbacia eggs. Krahl, Keltch, Neubeck, and Clowes (1941) reported a cytochrome oxidase enzyme, in the fertilized Arbacia egg, which can oxidize reduced cytochrome C. These authors demonstrated that this enzyme, when acting with cytoghrome C as a substrate, is inhibited completely by sodium cyanide or sodium azide, just as these agents depress cell division in the fertilized living Arbacia egg. In contrast, the total respiration can be inhibited only to a maximum of 70 to 80 per cent by cyanide and only about 50 per cent by azide.…”
Section: Introductionmentioning
confidence: 98%
“…Earlier works between 1877 and 1884 identified H 2 S as a “bacterial product” with its roles in intestinal and periodontal diseases, and more recently in regulating bacterial resistance to antibiotics. It was not until the 1940’s that H 2 S was identified as an inhibitor of cytochrome c oxidase (169). Only in the last two decades, have positive effects of H 2 S as a regulator of physiological functions, including the cardiovascular and nervous system, been identified.…”
Section: Historical Perspective Of No and H2s—overviewmentioning
confidence: 99%
“…See, however, Haber and Weiss ( 18 ) . 90 A SYMPOSIUM ON RESPIRATORY ENZYMES peroxide reaction contains the enzyme in the ferric state (61).…”
Section: Enzyme-substrate Intermediatesmentioning
confidence: 99%